Volume 2: I&C, Digital Controls, and Influence of Human Factors; Plant Construction Issues and Supply Chain Management; Pla 2017
DOI: 10.1115/power-icope2017-3194
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical and Experimental Study of HFE-7000 in a Small Scale Solar Organic Rankine Cycle As a Thermofluid

Abstract: Renewable energy technologies and sources have been playing a key role in reducing reliance on fossil fuels and significantly reducing CO 2 emissions and its footprint. EU initiative of generating 50% of the energy needs through sustainable sources by 2050 needs a direct response in terms of providing applied solutions to realize this target on time. Solar energy is one of the major and abundantly renewable energy sources which are free and clean. Solar energy can be utilized by means of solar Photovoltaic (PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The exergy analysis showed that the expander is the second-largest source of exergy losses in the system. Further experimental analysis and modeling results related to this expander were presented in [85]. Modeling results indicated that the pressure of the gas at the inlet to the expander has a significant impact on the efficiency of the ORC system and the efficiency of the solar collector.…”
Section: Bournemouth University (England)mentioning
confidence: 99%
See 1 more Smart Citation
“…The exergy analysis showed that the expander is the second-largest source of exergy losses in the system. Further experimental analysis and modeling results related to this expander were presented in [85]. Modeling results indicated that the pressure of the gas at the inlet to the expander has a significant impact on the efficiency of the ORC system and the efficiency of the solar collector.…”
Section: Bournemouth University (England)mentioning
confidence: 99%
“…At Bournemouth University (England), ORC systems adopting multi-vane expanders and driven by solar heat were tested. The research results were published in [84][85][86]. In [86], the results of experimental tests on an ORC test stand adopting a modified multi-vane pneumatic motor featuring a maximum power of 800 W and a maximum rotational speed of 4000 rpm were presented.…”
Section: Bournemouth University (England)mentioning
confidence: 99%